Determination of Prayer Times Through Islamic Astronomy Applications: Repositioning Traditional Authority in the Digital Era - Al Ayyubi, Ibnu Imam; Nurhikmah, Nurhikmah; Prayetno, Eko; Noerzanah, Firda; Musaldin, La Ode (Borneo International Journal of Islamic Studies, 2025)
The determination of prayer times is an important aspect of Islamic religious practices, typically approached through two methods: the traditional one based on the observation of the sun's position and the modern method using mathematical technology. This study aims to examine the shift in societal perspectives regarding prayer time determination based on Islamic Astronomy and the role of modern mathematical technology in influencing traditional authority. The research uses a qualitative approach with semi-structured interviews and document analysis. The study subjects consist of two groups: those who maintain traditional methods and those who adopt modern mathematical technology, with 40 purposively selected participants. The findings reveal that older generations tend to preserve traditional methods due to emotional and spiritual ties to religious heritage, while younger generations are more accepting of technology as a practical solution. Although technology facilitates the determination of prayer times, some people feel that its use diminishes the spiritual depth of the prayer experience. This study concludes that technology can serve as a supportive tool that enriches religious understanding without replacing the traditional values that exist.